Burckhardt among Basel, Berlin and Athens: the game of the Mirror - Moerbeck, Guilherme (História Revista, 2019)
This article is divided in two parts: in the first one, the focus will be young Jacob Burckhardt’s environment, his studies in Berlin under the supervision of Leopold von Ranke and some of his theoretic concerns around the Cultural History. The second part is to better understand how and why Burckhardt incorporated some of the main discussions of political theory from his own time, especially those of A. Tocqueville, J. Stuart Mill and Edmund Burke. We also aim to comprehend how the Swiss historian fashioned what I’m calling here: “the game of the mirror – from modernity to Ancient History”, i.e., the author’s reading of the Ancient World with a sort of disenchantment which came along with the process of modernization of Europe in the XIX’s.